MicroRNAs in breast cancer—new frontiers in diagnosis, targeted therapy, and prognosis assessment - Xiao, Jinsuo; Zhang, Lanhui; Su, Ruifan; Zhao, Bo; Dang, Yuanyuan; Zhao, Chuanlin; Wang, Sujin; Qi, Teng; Ji, Fuqing (Frontiers in Oncology, 2025)
Breast cancer is one of the most common malignancies among women globally, with an annually increasing incidence rate. Its complex pathogenesis and high heterogeneity pose significant challenges to clinical diagnosis and treatment. Traditional diagnostic methods and therapeutic approaches have limitations in improving patient survival rates and prognosis, thus urgently necessitating the identification of novel biomarkers and therapeutic targets. MicroRNA (miRNA), a class of endogenous non-coding small RNA molecules with a length of approximately 20–24 nucleotides, finely regulates gene expression by binding to the 3’ untranslated region of target mRNAs, inhibiting gene translation, or promoting mRNA degradation. In 2024, the Nobel Prize in Physiology or Medicine was awarded for research related to miRNA. Numerous studies have demonstrated that miRNAs play pivotal roles in the initiation, progression, invasion, metastasis, and drug resistance of breast cancer. Aberrant expression of specific miRNAs is closely associated with the molecular subtypes, prognosis, and treatment response of breast cancer, suggesting their potential as diagnostic and prognostic biomarkers. To explore the potential value of miRNA in the diagnosis and treatment of breast cancer, this article systematically reviews the latest research progress on the role of miRNAs in the diagnosis and treatment of breast cancer, with a focus on their application as tumor markers in early diagnosis, molecular subtyping, and therapeutic response monitoring. It elucidates the possibilities of miRNAs as therapeutic targets and tools in targeted therapy, including the current research status of miRNA mimics and inhibitors in breast cancer treatment. Furthermore, it analyzes the role of miRNAs in prognosis assessment, exploring their correlation with patient survival rates, recurrence risks, and treatment responsiveness. Additionally, this article discusses the challenges faced by miRNA research in precision medicine for breast cancer and future directions, providing new insights and strategies for early diagnosis, individualized treatment, and prognosis assessment of breast cancer.